Emerging Applications of Cellular Automata - Salcido, Alejandro (IntechOpen, 2013)
Cellular automata have become a core subject in the sciences of complexity due to their conceptual simplicity, easiness of implementation for computer simulation, and ability to exhibit a wide variety of amazingly complex behavior. These features of cellular automata have attracted the researchers attention from a wide range of divergent fields of science. In this book, six outstanding emerging cellular automata applications have been compiled. These contributions underline the versatility of cellular automata as models for a wide diversity of complex systems. We hope that, after reading the outstanding contributions compiled in this book, we will have succeeded in bringing across what engineers and scientists are now doing about the application of cellular automata for solving practical problems in diverse disciplines. We also hope that this book will have been to your interest and liking. Lastly, we would like to thank all the authors for their excellent contributions in the different topics of cellular automata covered in this book.